Association of herpesviruses and stroke: Systematic review and meta-analysis. - Harriet J Forbes; Elizabeth Williamson; Laura Benjamin; Judith Breuer; Martin M Brown; Sinéad M Langan; Caroline Minassian; Liam Smeeth; Sara L Thomas; Charlotte Warren-Gash (PLoS ONE, 2018)
Background Herpesviruses induce a range of inflammatory effects potentially contributing to an increased risk of stroke. Objectives To investigate whether patients with infection, or reactivation of, human herpesviruses are at increased stroke risk, compared to those without human herpesviruses. Data sources Six medical databases and grey literature sources from inception to January 2017. Study eligibility criteria Studies where the exposure was any human herpesvirus and the outcome was stroke. We included randomised controlled trials, cohort, case-control, case-crossover and self-controlled case series designs. Methods Meta-analyses when sufficiently homogeneous studies were available. Quality of evidence across studies was assessed. Results We identified 5012 publications; 41 met the eligibility criteria. Across cohort and self-controlled case series studies, there was moderate quality evidence that varicella infection in children was associated with a short-term increased stroke risk. Zoster was associated with a 1.5-fold increased stroke risk four weeks following onset (summary estimate: 1.55, 95%CI 1.46-1.65), which resolved after one year. Subgroup analyses suggested post-zoster stroke risk was greater among ophthalmic zoster patients, younger individuals and those not prescribed antivirals. Recent infection/reactivation of cytomegalovirus and herpes simplex viruses, but not past infection, was associated with increased stroke risk; however the evidence across studies was mainly derived from small, very low quality case-control studies. Conclusions Our review shows an increased stroke risk following zoster and suggests that recent infection or reactivation of other herpesviruses increases stroke risk, although better evidence is needed. Herpesviruses are common and potentially preventable; these findings may have implications for reducing stroke burden.